Low-loading Pt/β-Mo2C catalyst for ethanol dissociation. Experimental and theoretical characterization. Issue 41 (15th October 2021) - Chasvin, Nilda; Švenda, Petr; Pronsato, Estela; Diez, Alejandra; Volpe, María Alicia; Johánek, Viktor; Pistonesi, Carolina
Abstract : H2 production from ethanol adsorption on Mo2 C is increased by Pt. A low Pt loading on Mo2 C introduces strong modification. Abstract : The adsorption and dissociation of ethanol on Pt/β-Mo2 C with a low noble metal loading (0.1 wt%) is studied in the context of catalytic H2 production from alcohols. X-ray diffraction and experimental results indicate that Pt modifies the lattice parameters of β-Mo2 C. In line with this, density functional theory calculations indicate that the Mo–Mo distances are increased due to the presence of Pt. An experimental X-ray photoelectron spectroscopy study indicates that the chemical state of both molybdenum and carbon in Pt/β-Mo2 C are very different from those in the Pt-free carbide, which is also in agreement with the DFT results, which indicate that the Pt atoms generate a redistribution of charge density in their environment. Temperature programmed reaction analysis shows that at temperatures higher than 530 K, a two-fold increase in the production of H2, CH4 and C2 H6 is observed for Pt/β-Mo2 C as compared to β-Mo2 C, suggesting a higher catalytic activity for the Pt-containing carbide than for the pristine catalyst. Additionally, H2 production from ethanol on Pt/β-Mo2 C presents a higher activation energy (0.64 eV) than that corresponding to pristine molybdenum carbide. In agreement with this experimental result, climbing image-nudged elastic band (CI-NEB) calculations indicate that the energy barrier linked to the formation of H2 from ethanol increases with the presence of platinum. It is concluded that the low Pt loading notably modifies the catalytic pattern of molybdenum carbide, rendering it a highly active catalyst for ethanol decomposition.